The Effect Of User Experience And E-Service Quality On Shopee User Satisfaction In Indonesia. - Batti, V Marvel Joshua; Rachmawati, Indira (eProceedings of Management, 2025)
The expansion of e-commerce in Indonesia has intensified competition, especially for Shopee as a dominant platform. This research examines the influence of User Experience and E-Service Quality on Shopee user satisfaction in Indonesia. A quantitative method was applied, collecting data from 400 active Shopee users via questionnaires. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that dimensions of User Experience such as attractiveness, clarity, reliability, stimulation, and novelty significantly impact E-Service Quality. Moreover, E-Service Quality, including efficiency, system availability, fulfillment, and privacy, affects user satisfaction. This research provides insights for e-commerce platforms on optimizing service quality to enhance customer loyalty. Keywords: User Experience, E-Service Quality, User Satisfaction, Shopee, E-Commerce.